2018
DOI: 10.1002/tesj.378
|View full text |Cite
|
Sign up to set email alerts
|

This is my story: Latinx learners create digital stories during a summer literacy camp

Abstract: Educators need to create opportunities to develop English language learners’ (ELLs’) language skills through creative multiliteracy projects, identify ways to avoid summer loss, and harness the potential of parental engagement. The authors propose the use of a creative digital storytelling (DST) project to achieve these goals. The present case study draws upon a new literacy perspective to examine the impact of a DST project on a group of Latinx students in a summer literacy camp. Through examining the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Advances in technology have led to the digitalisation of storytelling and have resulted in the emergence of digital storytelling (DST), a multi-literacy practice of storytelling mediated by digital tools. In most cases DST results in the creation of a video output (Angay-Crowder et al 2013;Castanẽda et al 2018;Ohler 2013;Rubino et al 2018;Teehan 2006;Zellner 2018). Zellner (2018) piloted a DST intervention with her college students enrolled in an introductory astronomy course.…”
Section: Digital Storytelling and Science Disciplinary Literacy Develmentioning
confidence: 99%
“…Advances in technology have led to the digitalisation of storytelling and have resulted in the emergence of digital storytelling (DST), a multi-literacy practice of storytelling mediated by digital tools. In most cases DST results in the creation of a video output (Angay-Crowder et al 2013;Castanẽda et al 2018;Ohler 2013;Rubino et al 2018;Teehan 2006;Zellner 2018). Zellner (2018) piloted a DST intervention with her college students enrolled in an introductory astronomy course.…”
Section: Digital Storytelling and Science Disciplinary Literacy Develmentioning
confidence: 99%
“…In these studies, for example, it is investigated whether DST is a pedagogical tool for online inclusive pedagogy and reflective practice among students and teachers (Alcalá et al, 2016) or whether DST is an effective pedagogy or medium for student reflection in higher education (Austen et al, 2021), or whether a DST workshop as a multiliteracies practice can serve as a creative space for language learning (Castañeda et al, 2018).…”
Section: Research Issuesmentioning
confidence: 99%
“…In the context of the US, for children from immigrant families who speak a non-English home language, school provides a rich environment to develop English spoken language and reading skills. These dual-language speakers are thus found to be particularly vulnerable to school disruptions in their English literacy and other aspects of academic development (Castañeda et al, 2018;Hur & Suh, 2010;Lawrence, 2012). Experts have thus suggested that pandemic-related disruptions in schooling may be especially detrimental to bilingual speakers from immigrant families, noting that the pandemic limits both schooling access and also exacerbates other adversity factors such as the socioeconomic stability of immigrant families (e.g., Bao et al, 2020).…”
Section: Impacts Of Covid-19 On Language and Reading Development Amon...mentioning
confidence: 99%